Physico– Chemical Characterization of Pond Ash for Use as a Replacement of Cement in Concrete - P.Mahajan, Sarang; Kadam, Dr.Kshitija (International Journal of Innovative Research in Advanced Engineering, 2025)
Concrete is the second largest consumed material for construction due to encouraged growth of infrastructure worldwide. The preparation of concrete requires large amount of concrete making materials like cement, sand and coarse aggregate. Sand and Coarse aggregate are naturally available, but cement production involves heating of limestone and other materials to high temperatures leading to release of CO2 which in terns responsible for emission of greenhouse gases. Also, the utilization of natural resources leads to scarcity. This results in the creation of vast interest in the research area to utilize waste materials which could satisfy the criteria of strength and performance. Pond ash, a waste produced from thermal power plant, is one such material that can be used as a replacement of cement as well as fine aggregate partially or fully. To promote sustainable construction, study of physical and chemical properties of such waste material as a constituent in concrete is essential which ultimately addresses the issues related to disposal, environmental and ecological problems. Pond ash is potentially usable, but its properties depend on various factors like source of coal, type of boilers, type of coal grinding process adapted at power plant etc. This research focuses on the physical and chemical properties of pond ash like particle size distribution, specific gravity, bulk density, loss on ignition etc. to know its suitability for utilization in concrete. For this investigation, IS 3812(Part 1):2003, IS 1727, IS 2386 part -I, IS 2386 part -III are used.